Pengaruh Pembelajaran STEM Terhadap Keterampilan Berpikir Kritis dan Kreatif Siswa Kelas IV Sekolah Dasar - Nailinda, Vitra; Alim, Jesi Alexenader; Sekarwinahyu, Mestika (Indonesian Research Journal on Education, 2025)
This study aims to examine the effect of STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning on the critical and creative thinking skills of fourth-grade elementary school students. Specifically, it compares the improvement of these skills between students who participate in STEAM-based learning and those who receive conventional instruction. The research employs an experimental method with a pretest-posttest technique, using test questions as the instrument to assess critical and creative thinking abilities. The study follows a Nonequivalent Control Group Design, involving two classes: Class IV A as the experimental group and Class IV B as the control group. The results indicate a significant difference in critical thinking skills, with a 2-tailed significance value of 0.001 < 0.05, and in creative thinking skills, with a 2-tailed significance value of 0.012 < 0.05. These findings suggest that there is a difference in the average scores of critical and creative thinking skills between the two groups. Therefore, it can be concluded that HaH_a is accepted and HoH_o is rejected, meaning that the implementation of STEAM-based learning in the experimental class positively influences the improvement of elementary students' critical and creative thinking skills.